Neonatal T Helper 17 Responses Are Skewed Towards an Immunoregulatory Interleukin-22 Phenotype - Razzaghian, Hamid R.; Sharafian, Zohreh; Sharma, Ashish A.; Boyce, Guilaine K.; Lee, Kelsey; Da Silva, Rachel; Orban, Paul C.; Sekaly, Rafick-Pierre; Ross, Colin J.; Lavoie, Pascal M. (Frontiers in Immunology, 2021)
Newborns are frequently affected by mucocutaneous candidiasis. Th17 cells essentially limit mucosal invasion by commensal Candida spp. Here, we sought to understand the molecular basis for the developmental lack of Th17 cell responses circulating blood neonatal T cells. Cord blood CD4 T cells stimulated in Th17-polarizing conditions inherently produced high levels of the interleukin-22 immunoregulatory cytokine, particularly in the presence of neonatal antigen-presenting cells. A genome-wide transcriptome analysis comparing neonatal and adult naïve CD4 T cells ex vivo revealed major developmental changes in gene networks regulating Small Drosophila Mothers Against Decapentaplegic (SMAD) and Signal Transducer and Activator of Transcription 3 (STAT3) signaling in neonatal T cells. These changes were functionally validated by experiments showing that the requirement for TGF-β in human Th17 cell differentiation is age-dependent. Moreover, STAT3 activity was profoundly diminished and overexpression of the STAT3 gene restored Th17 cell differentiation capacity in neonatal T cells. These data reveal that Th17 cell responses are tightly regulated developmentally in humans in early life, at the gene expression level. These developmental changes may protect newborns against pathological Th17 cell responses, at the same time increasing their susceptibility to mucocutaneous candidiasis.